PENGARUH PELATIHAN DAN BUDAYA ORGANISASI TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INETRVENING PADA APARATUR SIPIL NEGARA DI UPT PUSKESMAS BESUKI - Nurwasilah, Siti; Arief, Mohammad Yahya; Syahputra, Hendra (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The research objective was to determine the effect of training and organizational culture on performance with job satisfaction as an intervening variable for state civil servants at UPT Puskesmas Besuki. The sampling technique used in this study is a saturated sample. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that training has a positive and significant effect on job satisfaction, organizational culture has a positive and significant effect on job satisfaction, training has a positive and significant effect on ASN performance, organizational culture has a negative and insignificant effect on performance ASN, job satisfaction has a positive and significant effect on ASN performance, training has a positive and significant effect on ASN performance through job satisfaction, organizational culture has a positive and significant effect on ASN performance through job satisfaction